Fixational eye movement waveforms in amblyopia: Characteristics of fast and slow eye movements - Sarah Linda Kang; Sinem B. Beylergil; Jorge Otero-Millan; Aasef Shaikh; Fatema Ghasia (Journal of Eye Movement Research)
Fixational eye movements comprise of fast microsaccades alternating with slow inter-saccadic drifts. These physiologic eye movements play an important role in visual perception.  Amblyopic patients are known to have fixation instability, particularly of the amblyopic eye. We examined eye movement abnormalities that contribute to this instability. We found that fixation stability is affected by the presence of fusion maldevelopment nystagmus (FMN). However, some amblyopes can have nystagmus without nasally directed slow phases and reversal in direction of the quick phase on ocular occlusion, features seen in FMN. In patients without nystagmus, we found increased amplitude of fixational saccades and inter-saccadic drifts. We categorized amblyopia patients by type (anisometropic, strabismic, or mixed) and eye movement waveform (no nystagmus, nystagmus without FMN, and FMN). We found specific fast and slow eye movement abnormalities of the fellow and amblyopic eye during fellow, amblyopic and both eyes viewing conditions across eye movement waveforms and types of amblyopia. These eye movement abnormalities can serve as biomarkers that can predict the impact of amblyopia as measured by visual acuity and stereopsis. Evaluation of fixational eye movements in amblyopia could be important to diagnose these common eye diseases and predict treatment effectiveness.